The Cyprus crisis and the problems of the Eurozone - de Espínola, José Ramón (Razón y fe, 2018)
After the bailouts of Greece, Ireland, Portugal and Spain, the rescue to Cyprus emerged in March 2013, and it seems that it will not be the last. Cyprus is a tiny country, its population represents only 0.26% of the population of the Eurozone and its GDP 0.19% of the GDP of the Eurozone. Despite this, its particular financial crisis and subsequent bailout have led to further turmoil in the already long Eurozone crisis. The case of Cyprus provides a new occasion to reflect on the effects of bubbles, the accumulation of debt, the errors and omissions of governments and banks, and on the immature governance of the Eurozone. In this article, after a few brief socio-political brushstrokes of Cyprus, the reason for its crisis is described. After that, the financial rescue plan for Cyprus, its errors and shortcomings, are analyzed. Finally, the article exposes the need for changes in European governance.